Upaya Pemerintah Desa Dalam meningkatkan Partisipasi Masyarakat Membayar Pajak Bumi dan Bangunan di Lemang Tandung La’Bo’ Kabupaten Toraja Utara - Saril Parinding; Theodorus Pangalila; Julien Biringan (CV. Kurnia Grup, 2026)
This study aims to examine and describe the steps taken by the Village Government in encouraging community involvement in the payment of Land and Building Tax (PBB) in Lembang Tandung La'bo', Sanggalangi District, North Toraja Regency. This research is motivated by the low compliance of citizens in fulfilling their obligation to pay the United Nations. Data shows that of the 1,053 registered taxpayers, there are 375 people who have not made payments on time. This study uses a qualitative method with data collection techniques through field observations, interviews, and documentation studies. The informants in this study include Village Heads, village officials, and communities with the status of taxpayers. The findings of the study show that various efforts made by the village government have not been fully effective in increasing community participation. The policies implemented tend to focus on direct collection and the implementation of administrative provisions, such as the distribution of Tax Payable Notices (SPPT) and the imposition of a fine of 2% every month for late taxpayers. On the other hand, counseling activities and providing understanding of tax functions and benefits, including openness in reporting the use of tax funds, have not been carried out optimally. The low participation of the community is also influenced by a number of factors, such as lack of awareness, limited economic conditions, the existence of taxpayers living outside the region, and problems with inaccurate data on tax objects. Based on these results, a more comprehensive approach is needed through strengthening planned and sustainable socialization, the implementation of educational collection methods, and increasing transparency in the management of tax funds so that public awareness and compliance can grow consistently.